The influence of landscape context on flora and arthropod fauna of winter cereal fields - Kovács, Anikó; Batáry, Péter; Báldi, András (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The effects of cultivation and landscape were studied on winter cereal fields in the Kiskunság National Park and surroundings. Botanical survey was conducted, spiders, ground-active beetles and bees were sampled with traps. To study the effects of landscape we determined the landscape diversity in 500-meter radius zone of the sampling points. According to statistical analyses the landscape diversity had positive impact on plants and negative impact on arthropods. There were higher diversity and abundance in the edge of the cereal fields than in the centre region.